(untitled) (Research, Society and Development, 2021)
The aim of the present study is to identify the evidence available in the literature about the practices carried out by the multidisciplinary team in palliative care during the COVID-19 pandemic. It refers to an integrative literature review study carried out in the following databases: Nursing Database (BDENF), Medical Literature Analysis and Retrieval Online System (MEDLINE) and Latin American and Caribbean Literature in Science of Health (LILACS). A temporal search was carried out for publications between the months of December 2020 and January 2021. The sample consisted of nine articles. The selected surveys were published in 2020, in English, and most of them were carried out in the United States of America (77.8%). As for the design of the studies, nine (100%) had a quantitative approach. After reading and summarizing the data, two categories emerged, namely: Practices and care provided to patients and families during the COVID-19 pandemic and Coping strategies by the multidisciplinary palliative care team. In this sense, the present study made it possible to understand the scarcity of physical and human resources observed during the worsening of the pandemic caused by COVID-19 and, consequently, the impact on the continuity of practices carried out by the palliative care team.